High Temperature Chlorosilane Corrosion of AISI 316L. Issue 8 (1st June 2016) - Aller, Josh; Ellingwood, Kevin; Jacobson, Nathan; Gannon, Paul
Abstract : Chlorosilanes are used at high temperatures throughout the world's semiconductor industries primarily as a way to refine and deposit silicon and silicon containing materials. They are most prevalent in the manufacture of solar grade polycrystalline silicon; an industry that has historically used high cost alloys to effectively handle corrosive chlorosilane species. This study focused on understanding the corrosion behaviors of AISI 316L stainless steel, a low cost alloy, in chlorosilane environments at a variety of industrially-relevant times (0–200 hours), temperatures (500–700°C), and hydrogen chloride (HCl) mole fractions (0.0–0.06). It was observed that AISI 316L can form either predominately metal chloride or metal silicide corrosion products depending on the mole fraction of HCl. Increasing temperatures tend to favor metal silicide formation, a trend predicted by thermodynamically generated predominance diagrams. Additionally, metal silicide surface layer growth appears to be diffusion controlled with an apparent parabolic rate at long times and high temperatures. There is also evidence for reaction-limited iron silicide formation at lower temperatures. Improved understanding of metals in high-temperature chlorosilane environments will help guide materials selection processes, and ultimately facilitate cost-competitive deployment of silicon-based photovoltaic systems.